Barley varieties registered in the Slovak Republic after the harvest of 2023 - Psota, Vratislav; Svorad, Marián; Garčárová, Markéta; Boško, Rastislav (KVASNY PRUMYSL, 2024)
After the harvest 2023, three varieties were registered in the Slovak Republic after three years of testing: the spring barley variety LG Rhapsody, the two-row winter barley variety Claudia, and the six-row winter barley variety MH Irén. The malting quality was determined for the varieties LG Rhapsody and Claudia. LG Rhapsody gave extract in malt dry matter of 83.2%. Proteolytic modification of this variety was high (Kolbach index 52.3%). The diastatic power (343 WK), the quality of the sweet wort (apparent final attenuation 82.1%), and the cytolytic modification (friability 94% and β-glucan content 60 mg/l) were at an optimal level. In all cases, the variety gave a clear sweet wort. The winter two-row barley variety Claudia gave a sweet wort with an extract of 81.5%. Kolbach index (46.2%) and diastatic power (508 WK) were at optimal levels. The quality of the sweet wort (apparent final attenuation 80.5%) and the cytolytic modification (friability 83% and β-glucan content of the wort 169 mg/l) were at an average level.